Satisfação Profissional das Equipes de Enfermagem atuantes na Sala de Vacina - Lima, Janaína Ferreira de (2023)
Professional satisfaction has been the subject of investigation and there are factors that influence professional satisfaction and dissatisfaction, associated with individual perceptions. Objective: To analyze the perceptions of health work that generate satisfaction and dissatisfaction in nursing teams working in vaccination rooms. Method: This is a qualitative and descriptive research. Data were collected from nursing teams working in vaccination rooms in eastern São Paulo during the months of March and April 2023. The information obtained was analyzed using descriptive statistics and content analysis, with the help of the IRAMUTEQ software. The project was approved by the Research Ethics Committee of the Federal University of São Carlos/UFSCar (CEP-UFSCar), under CAAE nº 65069722.5.0000.5504 and opinion nº 5.909.534. Results: 27 nursing professionals participated in this study, the majority of whom were female (92%), married (66%), with experience in the profession ranging from 6 months to 49 years. The experience in the vaccination room ranged from 2 months to 34 years. Two categories emerged from the Descending Hierarchical Classification (CHD): A and B, being: A) Aspects of Work Routines and B) Aspects of Satisfaction and Dissatisfaction at Work. Conclusion: It is possible to explore the aspects of work that generate professional satisfaction and reinforce them in order to remain positive factors. Likewise, it is possible to analyze the factors of dissatisfaction that need to be rethought and improved by management, adopting measures to carry out quality work.